Implementasi Kebijakan Program Jaminan Hari Tua (JHT) oleh Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Di Kota Medan - Ferdy Syahputra; Walid Musthafa Sembiring; Marlina Deliana (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
This thesis is entitled "Implementation of the Old Age Security Programme Policy by the Medan City Employment Social Security Administration Agency. The social security program is one of the responsibilities and obligations of the state to its people, which is adjusted to the condition of the state's financial capacity. Apart from that, the Social Security Program is also a form of social protection to ensure that all people can fulfill their basic needs and have a decent job. Old Age Security is a social security program that provides protection to participants against the risks that occur in old age, when the participant's productivity has decreased. However, in 2021 there is still a minimal level of participation in the North Sumatra region, especially in the informal sector. This research uses a qualitative method which is also called the naturalistic research method because the research is carried out in natural conditions (Natural Setting). In this study, the implementation of the Old Age Security Program policy by the Social Security Administrative Agency for Employment in Medan City was seen using Edward III's theory of communication, resources, dispositions, and bureaucratic structures that have been going well although not optimal, this can be seen from the uneven the communication carried out by the Medan City Employment BPJS to the community, especially for participation in the informal sector.